Characteristics and Quality of Life in Gynecologic Cancer Patients with Chemotherapy-induced Peripheral Neuropathy - Ju Hyeon Jeong; Ju Hee Nho; Gi Suk Kim; Young Eun Lee; Sun Young Yu; Hyun Ju Lee; Yu Mi Sim; Young Sun Lee (Korean Society of Women Health Nursing, 2013)
PURPOSE: The purpose of this study was to identify chemotherapy induced peripheral neuropathy, quality of life of patients with gynecologic cancer. METHODS: This was a cross-sectional survey design. We collected 130 patients with gynecologic cancer. They complete a self reported questionnaire including items related neuropathy and quality of life (FACT-GOG/Ntx subscale, FACT-G scale). RESULTS: The neuropathy score was 14.3+/-7.9. The quality of life score was 64.8+/-16.4. The neuropathy induced significant difference according to diabetic status, difficulties in performing household chores and willing to discontinuity of chemotherapy. And duration of cancer diagnosis, neuropathy, number of total chemo agent associated with quality of life. There was a negative correlation between number of total chemo agent and quality of life. Neuropathy independently affected quality of life. CONCLUSION: Chemotherapy induced peripheral neuropathy of patients with gynecologic cancer adversely affected women's quality of life and activities of daily living. To improve patient's quality of life, it is important that accurate assess and appropriately manage neuropathy in patients with gynecologic cancer.